Precooling does not enhance the effect on performance of midcooling with ice-slush/menthol - Riera, F.; Trong, T. T.; Rinaldi, K.; Hue, O. (International Journal of Sports Medicine, 2016)
This study investigated whether the combination of internal precooling (PC) and internal midcooling (MC cooling during exercise) would enhance performance more than MC alone. 9 trained males completed two 30-km cycling trials in a hot and humid environment (WBGT: 29±0.7°C, 80±0.02% relative humidity). For 30 min before exercise, the subjects sat quietly and drank water at 23°C (MC) or 3°C (PC+MC). During the MC and PC+MC time trials, they drank an ice-slush/menthol beverage (i. e., 0.025% menthol). Trial time, gastrointestinal temperature (T co ), heart rate (HR), rating of perceived exertion (RPE), thermal sensation (TS), and thermal comfort (TC) were assessed. Trial time was not significantly different (P>0.05) between MC and PC+MC (3 737±552 s and 3 815±455 s). Before exercise, T co was lower with precooling (37.0±0.3°C; P<0.02). During exercise, no between-trial differences were noted for T co , HR, RPE, TC or TS, but RPE was significantly lower with PC+MC in the latter stages (P<0.05). (1) Cold beverage intake before exercise did not improve the subsequent exercise performance with ice-slush/menthol beverage intake, and (2) despite no improvement in performance, RPE declined in the latter stages of exercise in the condition of PC+MC, suggesting that this combination might be beneficial for longer exercise.